PENGARUH REPUTASI AUDITOR, KEPEMILIKAN PUBLIK, AUDIT TENURE, DAN AUDIT DELAY TERHADAP AUDITOR SWITCHING SECARA VOLUNTARY - Fadjar Harimurti, Elisa Fajar Rohmah, Dewi Saptantinah Puji Astuti & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
This study aims to analyze whether there is a positive and significant influence, auditor reputation, public ownership, audit tenure and audit delay on auditor switching. Types of data in this study are quantitative data. Data sources in the study is financial reports and audit reports company property and real estate which is listed on Indonesia Stock Exchange during the period 2012 - 2016 published on website BEI (www.idx.co.id). The population in this study as many as 49 companies, the sampling technique used purposive sampling that is 30 companies. The technique of data analysis is statistic description, multicolinearutate test and logistic regression. The result of the research shows that: auditor reputation no significant effect on auditor switching, public ownership have a significant effect on auditor switching, audit tenure have a significant effect on auditor switching, audit delay no significant effect on auditor switching. Keywords: Auditor reputation, public ownership, audit tenure, audit delay, auditor switching